A flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wiring harness and its preparation process

By using modified silicone rubber materials in high-voltage wiring harness, a flame-retardant temperature-resistant layer and anti-aging sheath layer are formed, which solves the problem of insufficient performance of traditional silicone rubber under high temperature and ultraviolet light, and achieves higher high temperature resistance and flame-retardant and UV resistance.

CN119019848BActive Publication Date: 2025-02-14广东坚宝电缆有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479182.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The silicone rubber used in traditional high-voltage wire harnesses soften or melt in high temperature environments, lacks flame retardant performance, and has weak resistance to ultraviolet rays, resulting in limited application in harsh environments.

Method used

The modified silicone rubber material is tightly wrapped outside the wire core and sheath layer by extrusion continuous vulcanization, forming a flame-retardant and heat-resistant layer and an aging-resistant sheath layer to improve the material's high temperature resistance, flame-retardant and ultraviolet resistance.

Benefits of technology

Through the use of modified silicone rubber materials, the flame retardant, temperature resistance and UV aging resistance of high-voltage wire harnesses are improved, and their service life is extended and suitable for harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HPYANBD0M49D0KKVGYAB5QUVVTH4SOAHV6HYFM14
    Figure HPYANBD0M49D0KKVGYAB5QUVVTH4SOAHV6HYFM14
  • Figure LUJ0A0VBD0S8DLQUQXRTJ1SZENTRXBQURRJQFIWW
    Figure LUJ0A0VBD0S8DLQUQXRTJ1SZENTRXBQURRJQFIWW
Patent Text Reader

Abstract

The present invention discloses a flame-retardant, heat-resistant, and UV-resistant energy storage high-voltage wire harness and a preparation process thereof, and belongs to the technical field of energy storage high-voltage wire harnesses. The energy storage high-voltage wire harness comprises a wire core composed of multiple strands of copper monofilaments twisted together, the wire core is wrapped with a flame-retardant and heat-resistant layer, and the flame-retardant and heat-resistant layer is wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material A around the outside of the wire core to form a flame-retardant and heat-resistant layer; the anti-aging sheath layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material B around the outside of the flame-retardant and heat-resistant layer to form an anti-aging sheath layer. An energy storage high-voltage wire harness with excellent flame retardancy, heat resistance, and UV aging resistance is obtained by different modifications of silicone rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage high voltage wire harnesses, and in particular relates to a flame retardant, heat resistant and UV resistant energy storage high voltage wire harness and a preparation process thereof. Background Art

[0002] In today's society, with the continuous growth of electricity demand, high-voltage wire harnesses play a vital role in power transmission systems. However, traditional high-voltage wire harnesses often use silicone rubber as an insulating material. Although silicone rubber is widely used in many fields, it has some significant defects in high temperature resistance, flame retardancy and UV resistance. These shortcomings limit its application scope in harsh environments, making it unable to meet the use requirements in certain specific occasions. For example, in a high temperature environment, silicone rubber may soften or even melt, resulting in a decrease in its physical and mechanical properties and inability to continue to work normally. In addition, silicone rubber is also lacking in flame retardancy and is easy to burn, which is a big hidden danger in some environments that require fire safety. At the same time, silicone rubber has weak resistance to ultraviolet rays, and long-term exposure to ultraviolet rays will accelerate its aging process, thereby shortening the service life of the high-voltage wire harness. Therefore, in order to overcome these shortcomings, it is necessary to modify silicone rubber or find other alternative materials to meet the needs of application in harsh environments. Summary of the invention

[0003] The object of the present invention is to provide a flame retardant, heat resistant, UV resistant, energy storage high voltage wire harness and a preparation process thereof, so as to improve the flame retardant, heat resistant, UV resistant, and aging resistant properties of silicone rubber.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A preparation process of a flame-retardant, heat-resistant, and UV-resistant energy-storage high-voltage wire harness, the energy-storage high-voltage wire harness comprising a wire core formed by twisting multiple copper monofilaments, the wire core being wrapped with a flame-retardant and heat-resistant layer, the flame-retardant and heat-resistant layer being wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer is formed by tightly wrapping a modified silicone rubber material A around the wire core by extrusion and continuous vulcanization; the anti-aging sheath layer is formed by tightly wrapping a modified silicone rubber material B around the flame-retardant and heat-resistant layer by extrusion and continuous vulcanization.

[0006] As a preferred technical solution of the present invention, the preparation method of the modified silicone rubber material A comprises the following steps:

[0007] A1. Mix 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide, heat at 65°C for 5-7h, raise the temperature to 120°C and keep warm for 3-5h to obtain material A;

[0008] A2. Take the material A, dihydroxy polydimethylsiloxane, polymethylhydrogensilane, diethyl fumarate and platinum catalyst and mix them. Stir them for 100-180 minutes under the condition of vacuum degree of (-0.02MPa)-(-0.06MPa) to obtain the modified silicone rubber material A.

[0009] As a preferred technical solution of the present invention, the preparation method of the modified silicone rubber material B comprises the following steps:

[0010] B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 20-30 minutes, heat to 80°C, add cerium chloride solution, stir for 70-90 minutes to obtain material a;

[0011] B2, introducing carbon dioxide-nitrogen mixed gas into the material a until the pH of the system is 8, standing for 30-40 minutes, filtering, and taking the solid phase to obtain material b;

[0012] B3, take the material b, mix with deionized water, stir for 10-20min, adjust the pH to 6, keep warm at 80°C for 30-40min, filter, wash the solid phase, dry, and calcine at 250-300°C for 3-5h to obtain material c;

[0013] B4, take the material c, anhydrous ethanol, and KH-550 solution, mix them, stir them at 35-45°C for 3-4h, filter them, wash the solid phase, and dry them to obtain material d;

[0014] B5. Mix zinc nitrate hexahydrate, methanol and material d, stir for 10-12 hours, add 2-methylimidazole, ultrasonically disperse for 15-25 minutes, stand at room temperature for 24 hours, centrifuge, wash and dry the solid phase to obtain material e;

[0015] B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 8-10 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f;

[0016] B7, take 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst, mix them, connect them to a drying tower, isolate them from moisture and react for 24 hours, vacuum evaporation at 100°C, and vacuum distillation to obtain material g;

[0017] B8. Mix the material f, material g, methanol and aqueous ammonia, stir for 10-12 hours, and distill under reduced pressure at 100° C. to obtain material h;

[0018] B9. Take the material e and n-butanol, mix them, disperse them by ultrasonic for 15-25 minutes, add the material h, and keep warm at 60-80° C. for 20-30 minutes to obtain the modified silicone rubber material B.

[0019] As a preferred technical solution of the present invention, in step B1, the dosage ratio of the sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 90-95 g:1 L:40-50 mL; and the concentration of the cerium chloride solution is 0.3 mol / L.

[0020] As a preferred technical solution of the present invention, in step B2, the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3.

[0021] As a preferred technical solution of the present invention, in step B3, the mass ratio of the material b to deionized water is 8-10:1000.

[0022] As a preferred technical solution of the present invention, in step B4, the dosage ratio of the material c, anhydrous ethanol, and kh-550 solution is 4-6 g: 20-30 mL: 3-4 mL; the volume fraction of the kh-550 solution is 2%.

[0023] As a preferred technical solution of the present invention, in step B5, the mass ratio of zinc nitrate hexahydrate, methanol, material d, and 2-methylimidazole is 0.27-0.29:60-70:0.082-0.093:0.16-0.17.

[0024] As a preferred technical solution of the present invention, in step B6, the dosage ratio of tetramethoxysilane, hexamethyldisiloxane and ammonia water is 152-155g:128-132g:60g; the mass fraction of ammonia water is 1%.

[0025] As a preferred technical solution of the present invention, in step B7, the mass ratio of the 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane and platinum catalyst is 28-30:18-22:0.1-0.2.

[0026] As a preferred technical solution of the present invention, in step B8, the mass ratio of the material f, material g, methanol and aqueous ammonia is 4.8-5.2:30-40:40-50:2-3; the mass fraction of the aqueous ammonia is 8%.

[0027] As a preferred technical solution of the present invention, in step B9, the mass ratio of the material e, n-butanol and material h is 1-2:8-10:14-16.

[0028] As a preferred technical solution of the present invention, in step A1, the mass ratio of the 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane, and dibenzoyl peroxide is 3-4:0.6-0.8:0.02-0.03.

[0029] As a preferred technical solution of the present invention, in step A2, the mass ratio of material A, dihydroxypolydimethylsiloxane, polymethylhydrogensilane, diethyl fumarate and platinum catalyst is 2-5:30-40:2-3:0.2-0.4:0.13-0.15.

[0030] The flame-retardant, heat-resistant, UV-resistant, energy-storing high-voltage wire harness is manufactured using the above-mentioned preparation process.

[0031] Beneficial effects of the present invention:

[0032] The flame retardant, heat resistant, UV resistant, energy storage high voltage wiring harness and its preparation process disclosed in the present invention are as follows: 5,10,15,20-tetra(4-vinylphenyl)porphyrin with flame retardant effect which generates inert gas by combustion of doped N is copolymerized with monovinyl terminated polydimethylsiloxane, and then compounded with silicone rubber through a coupling agent, so that the cross-linking structure entanglement of the modified system is increased, the structure is more compact, the formed carbon layer is more compact, and a denser cross-linking network is formed. In addition, the introduction of N heteroatoms can decompose and release inert gas in a high temperature environment and dehydrate and carbonize the matrix, thereby improving the ablation resistance and flame retardant performance of the material; SiO formed by carbonization coprecipitation 2 -CeO 2 Composite, in which CeO 2 Nanoparticles embedded in SiO 2 In the framework, this overcomes the CeO 2 The anti-ultraviolet efficiency is reduced due to the agglomeration problem between the nanoparticles; at the same time, the epoxy-modified silicone rubber is introduced, so that the prepared metal skeleton and the epoxy group are arranged in the system through the ring-opening polymerization rule, which improves its impact resistance and anti-ultraviolet protection effect. Through different modifications of silicone rubber, an energy storage high-voltage wire harness with excellent flame retardancy, heat resistance and anti-ultraviolet aging is obtained. DETAILED DESCRIPTION

[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0034] Embodiment 1 A flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness and a preparation process thereof, comprising the following steps:

[0035] The energy storage high-voltage wire harness comprises a wire core composed of multiple strands of copper monofilaments twisted together, the wire core is wrapped with a flame-retardant and heat-resistant layer, and the flame-retardant and heat-resistant layer is wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material A around the outside of the wire core to form a flame-retardant and heat-resistant layer; the anti-aging sheath layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material B around the outside of the flame-retardant and heat-resistant layer to form an anti-aging sheath layer;

[0036] The preparation method of the modified silicone rubber material A comprises the following steps:

[0037] A1. Mix 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide, heat at 65°C for 5h, raise the temperature to 120°C and keep warm for 3h to obtain material A; the mass ratio of 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide is 3:0.6:0.02;

[0038] A2, take the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst, mix them, and stir them for 100 minutes under the condition of vacuum degree of -0.02MPa to obtain the modified silicone rubber material A; the mass ratio of the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst is 2:30:2:0.2:0.13;

[0039] The preparation method of the modified silicone rubber material B comprises the following steps:

[0040] B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 20 minutes, heat to 80°C, add cerium chloride solution, stir for 70 minutes, and obtain material a; the dosage ratio of sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 90g:1L:40mL; the concentration of cerium chloride solution is 0.3mol / L;

[0041] B2. A carbon dioxide-nitrogen mixed gas is introduced into the material a until the pH value of the system is 8, the mixture is allowed to stand for 30 minutes, filtered, and the solid phase is taken to obtain material b; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;

[0042] B3, take the material b and deionized water, mix, stir for 10 minutes, adjust the pH to 6, keep warm at 80°C for 30 minutes, filter, wash the solid phase, dry, and roast at 250°C for 3 hours to obtain material c; the mass ratio of the material b to deionized water is 8:1000;

[0043] B4, take the material c, anhydrous ethanol, and kh-550 solution, mix them, stir them at 35°C for 3h, filter them, wash the solid phase, and dry them to obtain material d; the dosage ratio of the material c, anhydrous ethanol, and kh-550 solution is 4g:20mL:3mL; the volume fraction of the kh-550 solution is 2%;

[0044] B5. Mix zinc nitrate hexahydrate, methanol and material d, stir for 10 hours, add 2-methylimidazole, ultrasonically disperse for 15 minutes, stand at room temperature for 24 hours, centrifuge, wash the solid phase, and dry to obtain material e; the mass ratio of zinc nitrate hexahydrate, methanol, material d and 2-methylimidazole is 0.27:60:0.082:0.16;

[0045] B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 8 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f; the dosage ratio of tetramethoxysilane, hexamethyldisiloxane and ammonia water was 152g:128g:60g; the mass fraction of ammonia water was 1%;

[0046] B7, take 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst, mix them, connect to a drying tower, isolate them from moisture and react for 24 hours, vacuum evaporation at 100°C, and vacuum distillation to obtain material g; the mass ratio of 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst is 28:18:0.1;

[0047] B8. Mix the material f, material g, methanol and ammonia water, stir for 10 hours, and distill under reduced pressure at 100°C to obtain material h; the mass ratio of the material f, material g, methanol and ammonia water is 4.8:30:40:2; the mass fraction of the ammonia water is 8%;

[0048] B9. Mix the material e and n-butanol, disperse them by ultrasonic for 15 minutes, add the material h, and keep warm at 60°C for 20 minutes to obtain the modified silicone rubber material B; the mass ratio of the material e, n-butanol, and material h is 1:8:14.

[0049] Example 2

[0050] A flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness and a preparation process thereof, comprising the following steps:

[0051] The energy storage high-voltage wire harness comprises a wire core composed of multiple strands of copper monofilaments twisted together, the wire core is wrapped with a flame-retardant and heat-resistant layer, and the flame-retardant and heat-resistant layer is wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material A around the outside of the wire core to form a flame-retardant and heat-resistant layer; the anti-aging sheath layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material B around the outside of the flame-retardant and heat-resistant layer to form an anti-aging sheath layer;

[0052] The preparation method of the modified silicone rubber material A comprises the following steps:

[0053] A1. Mix 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide, heat at 65°C for 6 hours, raise the temperature to 120°C and keep warm for 4 hours to obtain material A; the mass ratio of 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide is 3.5:0.7:0.025;

[0054] A2, take the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst, mix them, and stir them for 140 minutes under a vacuum degree of -0.04 MPa to obtain the modified silicone rubber material A; the mass ratio of the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst is 4:35:2.5:0.3:0.14;

[0055] The preparation method of the modified silicone rubber material B comprises the following steps:

[0056] B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 25 minutes, heat to 80°C, add cerium chloride solution, stir for 80 minutes, and obtain material a; the dosage ratio of sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 92g:1L:45mL; the concentration of cerium chloride solution is 0.3mol / L;

[0057] B2. A carbon dioxide-nitrogen mixed gas is introduced into the material a until the pH value of the system is 8, the mixture is allowed to stand for 35 minutes, filtered, and the solid phase is taken to obtain material b; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;

[0058] B3, take the material b and deionized water, mix, stir for 15 minutes, adjust the pH to 6, keep warm at 80°C for 35 minutes, filter, wash the solid phase, dry, and roast at 280°C for 4 hours to obtain material c; the mass ratio of the material b to deionized water is 9:1000;

[0059] B4, take the material c, anhydrous ethanol, and kh-550 solution, mix them, stir them at 40°C for 3.5h, filter them, wash the solid phase, and dry them to obtain material d; the dosage ratio of the material c, anhydrous ethanol, and kh-550 solution is 5g:25mL:3.5mL; the volume fraction of the kh-550 solution is 2%;

[0060] B5. Mix zinc nitrate hexahydrate, methanol, and material d, stir for 11 hours, add 2-methylimidazole, ultrasonically disperse for 20 minutes, stand at room temperature for 24 hours, centrifuge, wash the solid phase, and dry to obtain material e; the mass ratio of zinc nitrate hexahydrate, methanol, material d, and 2-methylimidazole is 0.28:65:0.087:0.165;

[0061] B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 9 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f; the dosage ratio of tetramethoxysilane, hexamethyldisiloxane and ammonia water was 153g:130g:60g; the mass fraction of ammonia water was 1%;

[0062] B7, take 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst, mix them, connect to a drying tower, isolate them from moisture and react for 24 hours, vacuum evaporation at 100°C, and vacuum distillation to obtain material g; the mass ratio of 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst is 29:20:0.15;

[0063] B8. Mix the material f, material g, methanol and ammonia water, stir for 11 hours, and distill under reduced pressure at 100° C. to obtain material h; the mass ratio of the material f, material g, methanol and ammonia water is 5.0:35:45:2.5; the mass fraction of the ammonia water is 8%;

[0064] B9. Take the material e and n-butanol, mix them, ultrasonically disperse them for 20 minutes, add the material h, and keep them warm at 70°C for 25 minutes to obtain the modified silicone rubber material B; the mass ratio of the material e, n-butanol and material h is 1.5:9:15.

[0065] Example 3

[0066] A flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness and a preparation process thereof, comprising the following steps:

[0067] The energy storage high-voltage wire harness comprises a wire core composed of multiple strands of copper monofilaments twisted together, the wire core is wrapped with a flame-retardant and heat-resistant layer, and the flame-retardant and heat-resistant layer is wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material A around the outside of the wire core to form a flame-retardant and heat-resistant layer; the anti-aging sheath layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material B around the outside of the flame-retardant and heat-resistant layer to form an anti-aging sheath layer;

[0068] The preparation method of the modified silicone rubber material A comprises the following steps:

[0069] A1. Mix 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide, heat at 65°C for 7h, raise the temperature to 120°C and keep warm for 5h to obtain material A; the mass ratio of 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide is 4:0.8:0.03;

[0070] A2, taking the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst, mixing, stirring for 180 minutes under the condition of vacuum degree of -0.06MPa, to obtain the modified silicone rubber material A; the mass ratio of the material A, dihydroxy polydimethylsiloxane, polymethyl hydrogen silane, diethyl fumarate, and platinum catalyst is 5:40:3:0.4:0.15;

[0071] The preparation method of the modified silicone rubber material B comprises the following steps:

[0072] B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 30 minutes, heat to 80°C, add cerium chloride solution, stir for 90 minutes, and obtain material a; the dosage ratio of sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 95g:1L:50mL; the concentration of cerium chloride solution is 0.3mol / L;

[0073] B2. A carbon dioxide-nitrogen mixed gas is introduced into the material a until the pH value of the system is 8, and the mixture is allowed to stand for 40 minutes, filtered, and the solid phase is taken to obtain material b; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;

[0074] B3, take the material b and deionized water, mix, stir for 20 minutes, adjust the pH to 6, keep warm at 80°C for 40 minutes, filter, wash the solid phase, dry, and roast at 300°C for 5 hours to obtain material c; the mass ratio of the material b to deionized water is 10:1000;

[0075] B4, take the material c, anhydrous ethanol, and kh-550 solution, mix them, stir them at 45°C for 4h, filter them, wash the solid phase, and dry them to obtain material d; the dosage ratio of the material c, anhydrous ethanol, and kh-550 solution is 6g:30mL:4mL; the volume fraction of the kh-550 solution is 2%;

[0076] B5. Mix zinc nitrate hexahydrate, methanol, and material d, stir for 12 hours, add 2-methylimidazole, ultrasonically disperse for 25 minutes, stand at room temperature for 24 hours, centrifuge, wash the solid phase, and dry to obtain material e; the mass ratio of zinc nitrate hexahydrate, methanol, material d, and 2-methylimidazole is 0.29:70:0.093:0.17;

[0077] B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 10 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f; the dosage ratio of tetramethoxysilane, hexamethyldisiloxane and ammonia water was 155g:132g:60g; the mass fraction of ammonia water was 1%;

[0078] B7, take 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst, mix them, connect them to a drying tower, isolate them from moisture and react for 24 hours, vacuum evaporation at 100°C, and vacuum distillation to obtain material g; the mass ratio of 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst is 30:22:0.2;

[0079] B8. Mix the material f, material g, methanol and ammonia water, stir for 12 hours, and distill under reduced pressure at 100°C to obtain material h; the mass ratio of the material f, material g, methanol and ammonia water is 5.2:40:50:3; the mass fraction of the ammonia water is 8%;

[0080] B9. Mix the material e and n-butanol, disperse them by ultrasonic for 25 minutes, add the material h, and keep warm at 80°C for 30 minutes to obtain the modified silicone rubber material B; the mass ratio of the material e, n-butanol, and material h is 2:10:16.

[0081] Comparative Example 1

[0082] The difference from Example 2 is that in the preparation process of the modified silicone rubber material A, monovinyl-terminated polydimethylsiloxane is not used to modify 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, and 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin is directly added to the original step A2.

[0083] Comparative Example 2

[0084] The difference from Example 2 is that material A is not added during the preparation of the modified silicone rubber material A.

[0085] Comparative Example 3

[0086] The difference from Example 2 is that, in the preparation process of the modified silicone rubber material B, only nitrogen is introduced in step B2.

[0087] Comparative Example 4

[0088] The difference from Example 2 is that the preparation method of the modified silicone rubber material B comprises the following steps:

[0089] B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 25 minutes, heat to 80°C, add cerium chloride solution, stir for 80 minutes, and obtain material a; the dosage ratio of sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 92g:1L:45mL; the concentration of cerium chloride solution is 0.3mol / L;

[0090] B2. A carbon dioxide-nitrogen mixed gas is introduced into the material a until the pH value of the system is 8, the mixture is allowed to stand for 35 minutes, filtered, and the solid phase is taken to obtain material b; the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:3;

[0091] B3, take the material b and deionized water, mix, stir for 15 minutes, adjust the pH to 6, keep warm at 80°C for 35 minutes, filter, wash the solid phase, dry, and roast at 280°C for 4 hours to obtain material c; the mass ratio of the material b to deionized water is 9:1000;

[0092] B4, take the material c, anhydrous ethanol, and kh-550 solution, mix them, stir them at 40°C for 3.5h, filter them, wash the solid phase, and dry them to obtain material d; the dosage ratio of the material c, anhydrous ethanol, and kh-550 solution is 5g:25mL:3.5mL; the volume fraction of the kh-550 solution is 2%;

[0093] B5. Mix zinc nitrate hexahydrate, methanol, and material d, stir for 11 hours, add 2-methylimidazole, ultrasonically disperse for 20 minutes, stand at room temperature for 24 hours, centrifuge, wash the solid phase, and dry to obtain material e; the mass ratio of zinc nitrate hexahydrate, methanol, material d, and 2-methylimidazole is 0.28:65:0.087:0.165;

[0094] B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 9 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f; the dosage ratio of tetramethoxysilane, hexamethyldisiloxane and ammonia water was 153g:130g:60g; the mass fraction of ammonia water was 1%;

[0095] B7. Take the material f, epoxy resin E51, methanol and ammonia water, mix them, stir for 11 hours, and distill under reduced pressure at 100°C to obtain material h; the mass ratio of the material f, material g, methanol and ammonia water is 5.0:35:45:2.5; the mass fraction of the ammonia water is 8%;

[0096] B8. Mix the material e and n-butanol, disperse them by ultrasonic for 20 minutes, add the material h, and keep warm at 70°C for 25 minutes to obtain the modified silicone rubber material B; the mass ratio of the material e, n-butanol, and material h is 1.5:9:15.

[0097] Performance Testing

[0098] 1) Take 100 parts of each of the modified silicone rubber materials A prepared in Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2, respectively, add 4 parts of hydroxy silicone oil and 0.5 parts of calcium stearate in a vacuum kneader, stir and knead at normal pressure and temperature of 70°C to form a mass, continue kneading for 20 minutes after massing, heat to 110°C, and knead for 1.5 hours at a vacuum degree of -0.8MPa, then cool and stand for 24 hours to obtain a mixed rubber, vulcanize at 165°C for 5 minutes, and then vulcanize at 180°C for 2 hours to obtain a flame retardant and heat-resistant layer, and perform a flame retardant performance test. The test results are shown in Table 1 below.

[0099] Table 1

[0100]

[0101] As can be seen from Table 1, the flame retardant and heat-resistant layer prepared from the modified silicone rubber material A prepared in Examples 1, 2 and 3 of the present application has a good flame retardant effect; the present application copolymerizes 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin with flame retardant effect which generates inert gas by combustion with doped N and monovinyl-terminated polydimethylsiloxane, and then compounds it with silicone rubber through a coupling agent, so that the cross-linking structure entanglement of the modified system is increased, the structure is tighter, the formed carbon layer is denser, and a denser cross-linking network is formed, and the introduction of N heteroatoms can decompose and release inert gas in a high temperature environment and dehydrate and carbonize the matrix, thereby improving the ablation resistance and flame retardant properties of the material.

[0102] 2) Take 100 parts of each of the modified silicone rubber materials B prepared in Example 1, Example 2, Example 3 and Comparative Example 3 and Comparative Example 4, respectively, add 4 parts of hydroxy silicone oil and 0.5 parts of calcium stearate in a vacuum kneader, stir and knead at normal pressure and temperature of 70°C to form a mass, continue kneading for 20 minutes after massing, heat to 110°C, and knead for 1.5 hours at a vacuum degree of -0.8MPa, then cool and stand for 24 hours to obtain a mixed rubber, vulcanize at 165°C for 5 minutes, and then vulcanize at 180°C for 2 hours to obtain an anti-aging sheath layer, and perform UV resistance and anti-aging tests. The test results are shown in Table 2 below.

[0103] Table 2

[0104]

[0105] As shown in Table 2, the anti-aging sheath layer prepared by the modified silicone rubber material B prepared in Examples 1, 2 and 3 of the present application has good anti-ultraviolet and anti-impact protection effects; the SiO 2 -CeO 2Composite, in which CeO 2 Nanoparticles embedded in SiO 2 In the framework, this overcomes the CeO 2 The anti-ultraviolet efficiency is reduced due to the agglomeration problem between the nanoparticles; at the same time, the epoxy-modified silicone rubber is introduced so that the prepared metal skeleton and the epoxy group are arranged in the system through ring-opening polymerization rules, thereby improving its impact resistance and anti-ultraviolet protection effect.

[0106] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A preparation process for a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness, characterized in that: The energy storage high-voltage wire harness comprises a wire core composed of multiple strands of copper monofilaments twisted together, the wire core is wrapped with a flame-retardant and heat-resistant layer, and the flame-retardant and heat-resistant layer is wrapped with an anti-aging sheath layer, characterized in that the flame-retardant and heat-resistant layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material A around the outside of the wire core to form a flame-retardant and heat-resistant layer; the anti-aging sheath layer adopts an extrusion continuous vulcanization method to tightly wrap the modified silicone rubber material B around the outside of the flame-retardant and heat-resistant layer to form an anti-aging sheath layer; The preparation method of the modified silicone rubber material A comprises the following steps: A1. Mix 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane and dibenzoyl peroxide, heat at 65°C for 5-7h, raise the temperature to 120°C and keep warm for 3-5h to obtain material A; A2, taking the material A, dihydroxy polydimethylsiloxane, polymethylhydrogensilane, diethyl fumarate, and platinum catalyst, mixing, and stirring for 100-180 minutes under the condition of vacuum degree of (-0.02MPa)-(-0.06MPa), the modified silicone rubber material A is obtained; The preparation method of the modified silicone rubber material B comprises the following steps: B1. Mix sodium metasilicate nonahydrate and deionized water, stir for 20-30 minutes, heat to 80°C, add cerium chloride solution, stir for 70-90 minutes to obtain material a; B2, introducing carbon dioxide-nitrogen mixed gas into the material a until the pH of the system is 8, standing for 30-40 minutes, filtering, and taking the solid phase to obtain material b; B3, take the material b, mix with deionized water, stir for 10-20min, adjust the pH to 6, keep warm at 80°C for 30-40min, filter, wash the solid phase, dry, and calcine at 250-300°C for 3-5h to obtain material c; B4, take the material c, anhydrous ethanol, and KH-550 solution, mix them, stir them at 35-45°C for 3-4h, filter them, wash the solid phase, and dry them to obtain material d; B5. Mix zinc nitrate hexahydrate, methanol and material d, stir for 10-12 hours, add 2-methylimidazole, ultrasonically disperse for 15-25 minutes, stand at room temperature for 24 hours, centrifuge, wash and dry the solid phase to obtain material e; B6, tetramethoxysilane, hexamethyldisiloxane and ammonia water were mixed, stirred for 8-10 hours, allowed to stand, and the oil phase was vacuum evaporated at 70°C for 2 hours to obtain material f; B7, take 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane, and platinum catalyst, mix them, connect them to a drying tower, isolate them from moisture and react for 24 hours, vacuum evaporation at 100°C, and vacuum distillation to obtain material g; B8. Mix the material f, material g, methanol and aqueous ammonia, stir for 10-12 hours, and distill under reduced pressure at 100° C. to obtain material h; B9. Take the material e and n-butanol, mix them, and disperse them by ultrasonic for 15-25 minutes. Then, add the material h, and keep warm at 60-80° C. for 20-30 minutes to obtain the modified silicone rubber material B.

2. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step B1, the dosage ratio of the sodium metasilicate nonahydrate, deionized water, and cerium chloride solution is 90-95g:1L:40-50mL; the concentration of the cerium chloride solution is 0.3mol / L; in step B2, the volume ratio of carbon dioxide to nitrogen in the carbon dioxide-nitrogen mixed gas is 1:

3.

3. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step B3, the mass ratio of the material b and deionized water is 8-10:1000; in step B4, the dosage ratio of the material c, anhydrous ethanol and kh-550 solution is 4-6g:20-30mL:3-4mL; the volume fraction of the kh-550 solution is 2%.

4. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step B5, the mass ratio of zinc nitrate hexahydrate, methanol, material d, and 2-methylimidazole is 0.27-0.29:60-70:0.082-0.093:0.16-0.17; in step B6, the dosage ratio of tetramethoxysilane, hexamethyldisiloxane, and ammonia water is 152-155g:128-132g:60g; and the mass fraction of ammonia water is 1%.

5. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step B7, the mass ratio of the 1,2-epoxy-4-vinylcyclohexane, trimethoxysilane and platinum catalyst is 28-30:18-22:0.1-0.2; in step B8, the mass ratio of the material f, material g, methanol and ammonia water is 4.8-5.2:30-40:40-50:2-3; the mass fraction of the ammonia water is 8%; in step B9, the mass ratio of the material e, n-butanol and material h is 1-2:8-10:14-16.

6. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step A1, the mass ratio of the 5,10,15,20-tetrakis(4-vinylphenyl)porphyrin, monovinyl-terminated polydimethylsiloxane, and dibenzoyl peroxide is 3-4:0.6-0.8:0.02-0.

03.

7. The preparation process of a flame-retardant, heat-resistant, UV-resistant, energy-storage high-voltage wire harness according to claim 1, characterized in that: In step A2, the mass ratio of material A, dihydroxypolydimethylsiloxane, polymethylhydrogensilane, diethyl fumarate and platinum catalyst is 2-5:30-40:2-3:0.2-0.4:0.13-0.

15.

8. A flame-retardant, heat-resistant, UV-resistant, energy-storing high-voltage wire harness made by the preparation process according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Flame retardant thermoplastic compositions having EMI shielding

    CN101535406A

  • Silicone rubber compositions

    CN102027069A